Safety assessment of after maternal exposure on male reproductive parameters in rats - Arruda, Aline de; Cardoso, Claudia Andrea de Lima; Vieira, Maria do Carmo; Arena, Arielle Cristina [UNESP] (Taylor & Francis, 2016)
Context: Hibiscus sabdariffa L. (Malvaceae) is a species widely used in folk medicine for the treatment of some disorders. Objective: This study evaluated the effects of H. sabdariffa (HS) on the development of the male reproductive tract in rats following in utero exposure. Materials and methods: Pregnant rats received 250 or 500 mg/kg of HS extract or vehicle from gestational day 12 until day 21 of lactation. Results and discussion: Both doses of HS increased the body weight of male offspring at weaning, without compromising the puberty onset parameters. At puberty, there was a significant increase in the vas deferens absolute weight and a significant reduction in the relative weight of kidney at higher dose. These animals also presented a significant reduction in the sperm number in the caput/corpus of epididymis after exposure to both doses and a reduction in the sperm number in the cauda epididymis for the lower dose. At adulthood, the highest dose significantly reduced the sperm production in relation to controls and both doses provoked a reduction in the relative sperm number in the epididymis without affecting the sperm morphology. Conclusion: These findings demonstrated that maternal exposure to H. sabdariffa can adversely influence the male reproductive system in rats.
Keywords: Herbal treatment; Lactation; Pregnancy; Sexual development; Toxicity